PENGARUH PEMBERIAN DOSIS EKSTRAK MENIRAN (Phyllanthus niruri L) TERHADAP TITER ANTIBODI NEWCASTLE DISEASE DAN AVIAN INFLUENZA PADA BROILER JANTAN - Heru Febryantono, Siswanto, Purnama Edy Santosa, dan Madi Hartono (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
This study was intended to know the effect of meniran (Phyllanthus niruri L) extract as an immunomodulator against avian influenza (AI) and newcastle disease (ND) antibody titers in male broilers, which was conducted in April 2019 to May 2019 at the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. Analysis of antibody titers was carried out at the Lampung Veterinary Virology Laboratory in Lampung. This study used Completely Randomized Design (CRD) with four treatments and five replications, those were drink water without Phyllanthus nirurilinn extract (P0), drink water with 1.5 mg/kg BW/day Phyllanthus niruri linn extract (P1), drink water with 3 mg/kg BW/day Phyllanthus niruri linn extract (P2), drink water with 4.5 mg/kg BW/day Phyllanthus niruri linn extract (P3). Based on variance analysis, the results of this study showed that the application of Phyllanthus niruri linn extract did not significantly affect on ND and AI antibody titers in male broilers. However, based on the average of antibody titer produced, giving Phyllanthus niruri linn extractat of 4.5 mg/kgBW/day can increase the AI antibody titer in male broilers. Keywords: Phyllanthus niruri linn, Immunomodulator, Antibody titer, Avian Influenza, Newcastle Disease, Male broiler